(untitled) (Romanian Studies Today, 2024)
The present paper aims to highlight distinctive characteristics related to teaching and learning Romanian as a foreign language, specifically focusing on two categories of words: false-friends and identical-meaning pairs, where primary stress shifts between Romanian and English. We focus on describing the stress system in these two languages, with both differences and similarities. The proposal presents an analysis of words falling into these two categories and illustrates the nuances of stress variation. Being aware of the difficulties experienced by foreign students while learning Romanian, we suggest a series of didactic methods and activities that can be integrated into Romanian as a foreign language course.